Admissions Quotas in Metropolitan Areas and Competition between Universities in Korea - Jae Hoon Kim (KDI Journal of Economic Policy, 2016)
The excessive demand for universities in metropolitan areas as a result of location premiums and regulated admissions quotas diminishes the competition between universities and the incentive to enhance educational performance to attract more students. Cases in point are the lower graduate employment rates (a measure of educational performance) of universities in metropolitan areas compared to those in non-metropolitan areas despite higher quality students. Additionally, the graduate employment rates of non-metropolitan universities are influenced by educational input factors such as an increase in the percentage of courses taught by full-time faculty, while those of metropolitan universities are contingent merely on enrollees' entrance scores. Ergo, a structure that revitalizes the competition between universities and encourages them to improve their educational services must be established in order to enhance the quality of higher education.
Keywords: I23; I28; 330; Admission Quotas; Disincentives to Compete; University Restructuring